Thermal Comfort Analysis Study At The Faculty Of Sports Science, Cenderawasih University, Jayapura-Papua - Piet Warkawani; Reza Fauzi; Nur Intan Simangunsong; Etty Indrawati (Journal of Synergy Landscape, 2023)
The area of the Faculty of Sports Science, University of Cenderawasih is the embodiment of Campus Open Space that must consider comfort for the needs of local users. This area consists of lecture buildings, entrepreneurship buildings, football stadiums, as well as several sports arenas such as volleyball, futsal, basketball, tennis and badminton arenas. The Campus of the Faculty of Sports Science has an area of 5 hectares in which there is open space. The purpose of this study is to determine the level of comfort in campus open spaces through measurements of air temperature, air humidity, wind speed influenced by land cover (vegetation, pavement, water elements and building orientation) in the campus environment. The theme of the study is the Comfort Zone which focuses on user comfort to achieve the goal or criteria of thermal comfort of the environment based on the placement of space and human activities in the campus landscape. This research method uses quantitative descriptive methods. Observations were made in several locations on campus open spaces by purposive sampling on each different land cover characteristic using quantitative methods to obtain the Temperature Humidity Index (THI) value. The results showed that uncomfortable locations according to THI value standards were in all locations due to the use of pavement materials that did not absorb heat or vegetation that grew not optimally. This research shows that the presence of vegetation that shades a location can have an impact on decreasing air temperature in that location.